2019
DOI: 10.3171/2018.3.jns172357
|View full text |Cite
|
Sign up to set email alerts
|

A rat study of the use of end-to-side peripheral nerve repair as a “babysitting” technique to reduce the deleterious effect of chronic denervation

Abstract: OBJECTIVE Functional recovery is disappointing after surgical repair of nerves that are injured far from their target organs and/or after delayed repair. In the former case, a nerve transfer that transects a distal nerve fascicle to innervate denervated targets is one strategy to promote nerve regeneration and functional recovery. An alternate strategy tested in this study is to perform an end-to-side neurorrhaphy to "babysit" (protect) the denervated distal nerve stump at the time of nerve repair and reduce t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…27 Multiple signaling molecules have been identified, which promote migration, among which neutrophins 28 and glial cell line derived neurotrophic factor are some of the most important. Rat models in which peripheral nerve conduits are seeded with such growth factors demonstrate improvements in regeneration 29,30 and functional recovery, 31 and it may be the absence of these factors in sufficient quantities at ANA graft sites, particularly where reconstruction is delayed, 32 which prevents adequate regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…27 Multiple signaling molecules have been identified, which promote migration, among which neutrophins 28 and glial cell line derived neurotrophic factor are some of the most important. Rat models in which peripheral nerve conduits are seeded with such growth factors demonstrate improvements in regeneration 29,30 and functional recovery, 31 and it may be the absence of these factors in sufficient quantities at ANA graft sites, particularly where reconstruction is delayed, 32 which prevents adequate regeneration.…”
Section: Discussionmentioning
confidence: 99%
“…After delayed repair of the proximal recipient nerve, 100% of native recipient motor axons regenerated into a distal recipient stump protected by cross-bridge nerve grafts. 10 The same authors showed that only 45% of native motor axons regenerated into a distal recipient stump after protection by a traditional ETS transfer 11 and about 40% after delayed ETE repair without protection. 10 They proposed that the amount of native recipient motor axon regeneration corresponds to the number of donor axons present in the recipient nerve-more donor axons means more recipient motor regeneration.…”
Section: Native Axon Regeneration After the Sets Transfermentioning
confidence: 98%
“…By contrast, in ETS transfers, the majority of donor axons remain undamaged while roughly a third of donor axons regenerate across the coaptation. 10,11 After both ETS and SETS coaptations, once axons enter the recipient nerve, they are subject to a similar regenerative environment. However, in SETS transfers, native recipient axons may also regenerate into the distal recipient nerve.…”
Section: Overview Of the Sets Growth Environmentmentioning
confidence: 99%
“…The phenotypic alterations of Schwann cells found in polyneuropathy patients similar to those seen after peripheral nerve injury emphasize the role of pathological remyelination patterns and impaired nerve regeneration in disease progression of polyneuropathy [ 11 , 13 , 34 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Decreased levels of neurotrophic factors and their receptors, alterations in cellular signaling pathways, and altered expression of cell adhesion molecules have been described as contributing factors [ 10 ]. The critical role of Schwann cells in peripheral nerve regeneration has been thoroughly investigated [ 11 , 12 ] and many of these findings translate to the development of polyneuropathy, as interactions between Schwann cells, axons and microvessels contribute to the disease [ 13 ]. Although much of the previous literature has been focused on axonopathy and vascular damage, the integral role of Schwann cells is gaining increasing evidence [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%